Low-Dose Paclitaxel Inhibits Tumor Cell Growth by Regulating Glutaminolysis in Colorectal Carcinoma Cells - Lv, Chaoxiang; Qu, Hao; Zhu, Wanyun; Xu, Kaixiang; Xu, Anyong; Jia, Baoyu; Qing, Yubo; Li, Honghui; Wei, Hong-Jiang; Zhao, Hong-Ye (Frontiers in Pharmacology, 2017)
Paclitaxel (PTX) is a natural alkaloid isolated from the bark of a tree, Taxus brevifolia, and is currently used to treat a variety of tumors. Recently, it has been found that low-dose PTX is a promising treatment for some cancers; presenting few side effects. However, antitumor mechanisms of low-dose PTX (<1 nM) have rarely been illuminated. Here we report a new antitumor mechanism of low-dose PTX in colorectal carcinoma cells. We treated colorectal carcinoma HCT116 cells with PTX at 0.1 and 0.3 nM for 0, 1, 2 and 3 days, and found that low-dose PTX inhibits cell growth without altering cell morphology and cell cycle. There was a significant decrease of pH in culture media with 0.3 nM PTX for 3 days. Also, lactate production was significantly increased in a dose and time-dependent manner. Furthermore, expression of glutaminolysis-related genes GLS, SLC7A11 and SLC1A5 were significantly decreased in the colorectal carcinoma cells treated with low-dose PTX. Meanwhile, protein expression levels of p53 and p21 increased significantly in colorectal carcinoma cells so treated. In summary, low-dose PTX down-regulated glutaminolysis-related genes and increased their lactate production, resulting in decreased pH of tumor microenvironments and inhibition of tumor cell growth. Up-regulation of p53 and p21 in colorectal carcinoma cells treated with low-dose PTX also contributed to inhibition of tumor cell growth.